E. R. Kellersberger, Medical Missionary to the Congo and the World (The journal of Presbyterian history, 2003)
That Christ may live in us, through us, giving us a special anointing for the Congo work. That we may practice the Presence of God always, every moment. Open the way for us to go to THY work and to OUR work in safety. May we be able to procure money in Bordeaux. May our baggage be kept safe and all our freight arrive intact at our mission station.